2004
DOI: 10.1074/jbc.m402648200
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved N-terminal Motif in Rad54 Is Important for Chromatin Remodeling and Homologous Strand Pairing

Abstract: The Swi2/Snf2-related protein Rad54 is a chromatin remodeling enzyme that is important for homologous strand pairing catalyzed by the eukaryotic recombinase Rad51. The chromatin remodeling and DNA-stimulated ATPase activities of Rad54 are significantly enhanced by Rad51. To investigate the functions of Rad54, we generated and analyzed a series of mutant Rad54 proteins. Notably, the deletion of an N-terminal motif (amino acid residues 2-9), which is identical in Rad54 in Drosophila, mice, and humans, results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
1
27
1
Order By: Relevance
“…Importantly, we and others have presented evidence that the flexible N-terminus of Rad54 harbors the Rad51 interaction domain [28,29]. We have shown here that the histone H3 tail binding domain likewise resides within the N-terminus of Rad54.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Importantly, we and others have presented evidence that the flexible N-terminus of Rad54 harbors the Rad51 interaction domain [28,29]. We have shown here that the histone H3 tail binding domain likewise resides within the N-terminus of Rad54.…”
Section: Discussionsupporting
confidence: 57%
“…The promotion of Rad51-mediated homologous DNA pairing and strand exchange by Rad54 requires the ATPase activity of the latter and physical interaction between these two HR factors [27][28][29]. Interestingly, Rad54 dissociates Rad51 from duplex DNA via its DNA translocase activity, a function believed to be important for the intracellular recycling of Rad51 and possibly for freeing the primer end in the D-loop structure to initiate the DNA synthesis reaction [30].…”
Section: Introductionmentioning
confidence: 99%
“…This finding and the fact that Rdh54 neither binds nor functionally synergizes with the E. coli RecA protein (13) (this work) are consistent with the premise that specific complex formation between Rdh54 and Rad51 is a prerequisite for functional interactions between these two S. cerevisiae HR factors. Previous studies have shown that complex formation of Rad54 with Rad51 is required for functional synergy between these two recombination factors (14,33,38,39,(41)(42)(43)(44), and Rdh54 (13) (this work) resembles Rad54 in this regard.…”
Section: Discussionmentioning
confidence: 75%
“…Even though Rad51 removal in the in vitro setting is not absolutely contingent upon Rdh54 possessing the ability to bind Rad51, within cells, complex formation with Rad51 may well be necessary for efficient targeting of Rdh54 to chromosome locales where Rad51 is bound. As noted earlier, complex formation of Rad54 with Rad51 appears to be indispensable for functional synergy between them (14,33,38,39,(41)(42)(43)(44). It will be important to test whether variants of Rad54 that lack the ability to interact with Rad51 (38,39) are capable of clearing Rad51 from dsDNA.…”
Section: Discussionmentioning
confidence: 99%
“…These SNF2-like ATPases are broadly conserved throughout evolution and share a common core ATPase domain. Whereas the core motor ATPase domain provides the driving force for DNA translocation and chromatin-remodeling activity, emerging evidence suggests important roles of the flanking regions in mediating specific interactions with nucleosomes or other protein factors, substrate specificity, and the regulation of the function of the motor (2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%